2016
DOI: 10.15671/hjbc.20164420572
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antioxidant, Xanthine Oxidase and Urease Inhibitory Activities of Some Chlorine Containing Benzimidazoles

Abstract: Ö Z E T B ir seri tetra-substitüe benzimidazol türevi sentezlendi ve üreaz inhibisyon, anti-ksantin oksidaz (XO) ve antioksidan aktiviteleri incelendi. Bazı bileşiklerin önemli derecede antioksidan aktivite gösterdiği tespit edildi. Özellikle, bileşik 4, 5a, 5b, 5c, 5d ve 6b ABTS•+ radikal katyon temizleme (SC 50 : 9.51-70.43 µg/mL) ve bakır indirgeyici antioksidan kapasite (CUPRAC) tayininde yüksek derecede aktivite gösterdiği belirlendi. Bileşik 6d ise, 125 µg/mL derişimde en yüksek anti-ksantin oksidaz (XO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Urease is an enzyme that catalyzes the hydrolysis of urea into carbon dioxide and ammonia. The production of ammonia was measured by indophenol method and used to determine the urease inhibitory activity . The percentage remaining activity was calculated from the formula: % Remaining Activity = [(OD test )/(OD control ) × 100].…”
Section: Methodsmentioning
confidence: 99%
“…Urease is an enzyme that catalyzes the hydrolysis of urea into carbon dioxide and ammonia. The production of ammonia was measured by indophenol method and used to determine the urease inhibitory activity . The percentage remaining activity was calculated from the formula: % Remaining Activity = [(OD test )/(OD control ) × 100].…”
Section: Methodsmentioning
confidence: 99%
“…20 Also, fluorine containing 1,2,4-triazole-5-on derivatives and benzimidazole derivatives has been reported that exhibited good inhibition activity on XO. 21,22…”
Section: Anti-xanthine Oxidase Activitymentioning
confidence: 99%
“…Urease is an enzyme that catalyzes the hydrolysis of urea into carbon dioxide and ammonia. The production of ammonia was measured by indophenol method and used to determine the urease inhibitory activity (25, 26,27). The percentage remaining activity was calculated from the formula % Remaining Activity = [(ODtest)/(ODcontrol)x100].…”
Section: Urease Inhibition Assaymentioning
confidence: 99%